Vitamin B12-functionalized patterned Si surface for solar energy conversion - Smertenko, P.S.; Roshchina, N.M.; Kuznetsova, D.A.; Barsukov, V.Z.; Wisz, G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The interaction between organic and inorganic materials is very relevant both for understanding their nature and for some applications. One of the directions in this area is the functionalization and sensitization of semiconductor surfaces by organic compounds for solar energy conversion. The main goal of this research is to demonstrate the possibility of immobilizing some photofunctional organic compounds on an inorganic silicon substrate at room temperature. In particular, we have prepared a new B12–Si hybrid with the solar conversion efficiency up to Eff = 3.75% at room temperature by chemical deposition of vitamin B12 on the patterned silicon substrate. Here, we report the correlation between morphology and functionality, as well as deposition mode for B₁₂–Si hybrids.